The social contents of gender stereotypes in term of authoritative influence - Svitlana Zagurska (Cхід, 2016)
The social factors of gender stereotypes implementation in term of authoritative influence have been analyzed. The contents of gender stereotypes as a social category and their functional orientation have been determined. The author analyzes gender schemes: they are based on coding of "we" and "other", it's important for social reality understanding. The role of gender stereotypes in producing and maintaining society hierarchical relationships also has been described. The social contents of gender roles have been defined. The author emphasizes their meaning in term of social behaviors. In modern conditions of Ukrainian society it is obvious that gender issues can't be covered primarily as an object of psychological research, but it also needs a social and philosophical reflection.